Comparative Study of several physical and skillful variables between the National Center for Sports Talent Care for football and Amu Baba School for the ages (12-13) years - Musa, Mahmoud; Abdul latif, Deyaa (Journal of Physical Education, 2015)
Football is characterized with the variety physical and skillful variables , the significance and the fundamental basis to develop the performance of the Footballer , so the development of these variables need to continuity in the process of training with executing the tests regularly and continuously. Any kind of weakness in these variables will lead to weakness and low , as well , in the level of skillful and physical Footballer ' performance. As the player can not keep up with the training requirements of training well as it is required strength , speed and compatibility in performance. The research problem is determined in the lack of studies and research that take care of comparison between the National Center for Sports Talent Care for football and Amu Baba School in terms of being variables of the study, for the purpose of developing a scientific study and by depending on codified tests in front of coaches of the National Center for Sports Talent Care for football and Amu Baba School , the researcher has proposed studying this problem through the development of a comparative study of the physical , Kinetic , and skillful variables and between the National Center for Sports Talent Care for football and Amu Baba School with knowledge and recognizing the differences between them, hoping that this will be a simple addition and scientific that researcher puts it in front of Trainers of specialized the National Center for Sports Talent Care for football and Amu Baba School. The research aims to: identify some of the physical, kinetic and skillful variables and the results of test the National Center for Sports Talent Care for football and Amu Baba School for the ages 12-13 years and Identify and understand the differences between the National Center for Sports Talent Care for football and Amu Baba School Reconstruction 12-13 years for some physical and dynamic variables. Through action research, the researcher has used the descriptive manner by style of comparison where sample of research consisted of players of the National Center for Sports Talent Care for football and Amu Baba School by 40 player , (20) player for each school for the ages 12-13 years. The rhythm etic mean and standard of deviation and median and torsion test and T-test as statistic means The most important results of the research was clear Weakness to score goals (Scoring) for the sample of research , Significant differences between them did not show. Researcher has made" propose'' many recommendations , the most important are: attention skillfully scoring by Coaches of the National Center for Sports Talent Care for football and Amu Baba School During the training modules as having great significance in Football Game